Analisis Energi Gas Engine Siklus Miller Dengan Bahan Bakar Biogas Berbahan Baku POME - Atikah Purwantari; Romy Romy; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Biogas Power Plant comes with a form of alternative energy handling efforts originating from POME Because of the engine is continuously operated without stopping, it requires maintenance so that the engine's performance is maintained properly. The decrease in engine performance produces wasted energy so that engine efficiency is not optimal. In addition, the maintenance process takes a long time until the engine can be operatedagain. This is a problem because the maintenance process is carried out on all cylinder engines. The purpose of this study is to calculate and analyze the energy on the left and right exhaust on the gas engine Guascor SFGM 560 Miller Cycle. From the analysis, the biggest energy efficiency is in the left cylinder in the first period which was59.82% at 15.00 PM. and as a comparison in second period the highest efficiency is at 12.00 that was equal to 66.45%.Keywords: miller cycle, biogas, gas engine, energy, effisiensi energy